2022
DOI: 10.1186/s12874-022-01646-1
|View full text |Cite
|
Sign up to set email alerts
|

Standard of care for COVID-19 in randomized clinical trials registered in trial registries and published in preprint servers and scholarly journals: a cross-sectional study

Abstract: Background The concept of standard of care (SoC) treatment is commonly utilized in clinical trials. However, in a setting of an emergent disease, such as COVID-19, where there is no established effective treatment, it is unclear what the investigators considered as the SoC in early clinical trials. The aim of this study was to analyze and classify SoC reported in randomized controlled trial (RCT) registrations and RCTs published in scholarly journals and on preprint servers about treatment inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the most recent analysis of the pharmacological therapies in 737 unique clinical trials indicated that the most commonly used interventions for COVID- 19 patients were drugs such as antiparasitics (62% of the trials), antivirals (57%), antibiotics (31%), oxygen (17%), antithrombotics/anticoagulants (14%), vitamins (13%), immunomodulatory agents (13%), glucocorticoids (12%), analgesics/antipyretics (12%). Moreover, various combinations of those interventions were used, with up to seven different types of combinations [37] .
Fig.
…”
Section: Current Pharmacological Therapies Against Covid-19mentioning
confidence: 99%
“…Interestingly, the most recent analysis of the pharmacological therapies in 737 unique clinical trials indicated that the most commonly used interventions for COVID- 19 patients were drugs such as antiparasitics (62% of the trials), antivirals (57%), antibiotics (31%), oxygen (17%), antithrombotics/anticoagulants (14%), vitamins (13%), immunomodulatory agents (13%), glucocorticoids (12%), analgesics/antipyretics (12%). Moreover, various combinations of those interventions were used, with up to seven different types of combinations [37] .
Fig.
…”
Section: Current Pharmacological Therapies Against Covid-19mentioning
confidence: 99%
“…In particular, there are many and different regulatory and other approaches for the introduction of drug treatments in millions of patients with chronic and untreatable diseases [51][52][53][54][55][56], in emergency medicine and also in orphan diseases [57][58][59][60][61][62], where drug cost is an important parameter [59][60][61][62]. Many examples of such approaches include the call for emergency medicines in the recent COVID-19 pandemic [63] and the expanding area of drug repurposing [64] in many other untreatable diseases [59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%